Social Brain Development in Williams Syndrome: The Current Status and Directions for Future Research - Haas, Brian W.; Reiss, Allan L. (Frontiers in Psychology, 2012)
Williams syndrome (WS) is a neurodevelopmental condition that commonly occurs as a result of a contiguous deletion of approximately 26-28 genes on chromosome 7q11.23. WS is often associated with a distinctive psychological phenotype characterized by abnormal face, emotion and social-cognitive functioning. In this article, we review available studies investigating the social phenotype of WS throughout development and neuroimaging studies investigating brain structure and function as related to social and emotional functioning in this condition. This review highlights several neuro-behavioral mechanisms that may be related to abnormal social development in WS. In particular, we discuss how abnormal social behavior in WS may be related to abnormalities in the cortical representation of faces, connectivity within the ventral stream, structure and function of the amygdala and how long- and short-range connections develop. We draw support from research on typical brain development and from existing behavioral and neuroimaging research on WS. We conclude with a discussion of how genes and environmental factors might interact to influence social brain development in WS and how future neuroimaging and behavioral research can inform further elucidate social brain development in WS. Lastly, we describe how ongoing studies may translate to improved social developmental outcomes for individuals with WS.